Composite current collector, solid-state battery, and electric device
Patent Information
- Application Number
- CN202610860796.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-13
AI Technical Summary
在固态电池中,铜箔作为复合集流体材料,在固态电池中起着承载活性材料、传导电子的作用,然而,以硫化物为固态电解质的固态电池中,硫化物与水或氧气反应生成硫化氢气体会腐蚀铜箔,生成硫化铜,从而导致电阻上升甚至电池失效;其次,铜箔在高压下机械性能不足,存在断裂的风险,影响电池的寿命;再次,固态电池的负极活性材料在充放电过程中发生显著的体积膨胀、收缩,电解铜箔难以承受反复的膨胀和收缩,导致铜箔易于断裂或粉化,影响电池的循环寿命和容量保持率
[0020]与现有技术相比,本申请的有益效果为:本申请的复合集流体中第一镍层的粒状晶通过晶界阻碍位错运动提升抗拉强度,第二镍层的柱状晶沿复合集流体的厚度方向生长,提高第二镍层的断裂韧性和抗裂纹扩展能力,从而提高复合集流体的韧性;含有粒状晶的第一镍层与含有柱状晶的第二镍层构成的结构在复合集流体厚度方向上形成模量渐变,使外力在界面处逐级耗散,显著提高复合集流体的抗拉强度,同时可以阻止腐蚀介质渗透,从而提高复合集流体的耐腐蚀性;其次,通过控制第一镍层的厚度d1与第二镍层的厚度d2满足:d2/d1=1.5~4.0,对镍层实现非对称的厚度设计,在复合集流体内部引入压应力,抵消外部应力,实现应力平衡,提高第一镍层和金属基层之间的结合力。
Smart Images

Figure CN122907643A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical energy storage technology, specifically to composite current collectors, solid-state batteries, and electrical devices. Background Technology
[0002] With technological advancements, people have increasingly higher demands for the driving range, range efficiency, and safety performance of new energy vehicles. Traditional batteries, which primarily use liquid electrolytes, are prone to safety issues such as leakage, smoke, fire, and explosion under conditions of high temperature, overcharging, nail penetration, and impact from heavy objects. Solid-state batteries (ASBs), by using solid electrolytes instead of liquid electrolytes, eliminate electrolyte leakage, significantly improving battery safety and thus becoming a promising alternative. In solid-state batteries, copper foil, as a composite current collector, plays a crucial role in carrying active materials and conducting electrons. However, in solid-state batteries using sulfides as the solid electrolyte, the reaction of sulfides with water or oxygen to generate hydrogen sulfide gas corrodes the copper foil, forming copper sulfide, which leads to increased resistance and even battery failure. Secondly, copper foil lacks sufficient mechanical properties under high voltage, posing a risk of breakage and affecting battery life. Thirdly, the negative electrode active material in solid-state batteries undergoes significant volume expansion and contraction during charge and discharge, and electrolytic copper foil cannot withstand repeated expansion and contraction, making it prone to breakage or pulverization, thus affecting the battery's cycle life and capacity retention. Therefore, there is an urgent need to develop a novel composite current collector suitable for solid-state battery systems. Summary of the Invention
[0003] The purpose of this application is to overcome the shortcomings of the prior art and to provide composite current collectors, solid-state batteries and electrical devices.
[0004] To achieve the above objectives, the technical solution adopted in this application is as follows: In the first aspect, a composite current collector is provided, comprising a metal substrate and a first nickel layer and a second nickel layer sequentially stacked on at least one side surface of the metal substrate; The thickness d1 of the first nickel layer on one side and the thickness d2 of the second nickel layer on one side satisfy: d2 / d1 = 1.5~4.0; The average grain size a of the first nickel layer and the average grain size b of the second nickel layer satisfy: a <b,a<80nm; The first nickel layer has granular crystals, and the second nickel layer has columnar crystals.
[0005] In some embodiments, the thickness d1 of the first nickel layer on one side, measured in nm, satisfies: 100≤d1≤300; and the thickness d2 of the second nickel layer on one side satisfies: 300≤d2≤800.
[0006] In some embodiments, the average grain size a of the first nickel layer, measured in nm, satisfies: 15 ≤ a ≤ 65, and the average grain size b of the second nickel layer satisfies: 70 ≤ b ≤ 185.
[0007] In some embodiments, the texture factor TC(111) of the (111) crystal plane of the first nickel layer satisfies: TC(111)≥45%; the texture factor TC(200) of the (200) crystal plane of the second nickel layer satisfies: TC(200)≥38%.
[0008] In some embodiments, the composite current collector includes a nickel-phosphorus alloy layer disposed between the metal substrate and the first nickel layer.
[0009] In some embodiments, the thickness d3 of the nickel-phosphorus alloy layer on one side, measured in nm, satisfies: 5 ≤ d3 ≤ 20; And / or, the mass percentage P of phosphorus in the nickel-phosphorus alloy layer satisfies: 4% ≤ P ≤ 10%.
[0010] In some implementations, at least one of the following (a) to (c) is satisfied: (a) In μm, the thickness d4 of the metal substrate satisfies: 3≤d4≤8; (b) The first nickel layer and the second nickel layer are each made of nickel or a nickel alloy independently; (c) The metal base layer is made of copper or copper alloy.
[0011] Secondly, a method for preparing the aforementioned composite current collector is provided, comprising the following steps: Preparation of the first nickel layer: A first nickel layer is deposited on the surface of at least one side of the metal substrate using a first electrodeposition method; Preparation of the second nickel layer: A second nickel layer is deposited on the surface of the first nickel layer using a second electrodeposition method; In the step of preparing the first nickel layer, the first electrodeposition is carried out in the first electroplating solution, which includes 1,4-butynediol.
[0012] In some embodiments, the first electroplating solution comprises the following components at mass concentrations: nickel sulfate 200-300 g / L, nickel chloride 30-50 g / L, boric acid 30-40 g / L, saccharin 0.2-2 g / L, and 1,4-butynediol 0.05-0.5 g / L.
[0013] In some embodiments, in step S3, the second electrodeposition is carried out in a second electroplating solution comprising the following components at mass concentrations: nickel sulfate 250-350 g / L, nickel chloride 40-60 g / L, boric acid 35-45 g / L, and sodium dodecyl sulfate 0.05-0.2 g / L.
[0014] In some embodiments, the first electrodeposition is pulse electrodeposition; the second electrodeposition is direct current electrodeposition.
[0015] In some embodiments, the process parameters for the pulse electrodeposition are as follows: current density of 5-10 A / dm³. 2 The duty cycle is 20-50%, and the frequency is 200-500Hz.
[0016] In some embodiments, the step of preparing a nickel-phosphorus alloy layer is also included, which is performed before the step of preparing the first nickel layer; the step of preparing the nickel-phosphorus alloy layer is as follows: depositing the nickel-phosphorus alloy layer on the surface of at least one side of the metal substrate using a chemical deposition method.
[0017] In some embodiments, the chemical deposition is carried out in a chemical deposition solution comprising the following components at mass concentrations: nickel sulfate 20-30 g / L, sodium hypophosphite 25-35 g / L, sodium citrate 15-25 g / L, and sodium acetate 10-20 g / L.
[0018] Thirdly, a solid-state battery is provided, comprising the aforementioned composite current collector or a composite current collector prepared by the method for preparing the aforementioned composite current collector.
[0019] Fourthly, an electrical device is provided, including the aforementioned solid-state battery.
[0020] Compared with the prior art, the beneficial effects of this application are as follows: In the composite current collector of this application, the granular crystals of the first nickel layer hinder dislocation movement through grain boundaries, thereby improving tensile strength. The columnar crystals of the second nickel layer grow along the thickness direction of the composite current collector, improving the fracture toughness and crack propagation resistance of the second nickel layer, thereby improving the toughness of the composite current collector. The structure formed by the first nickel layer containing granular crystals and the second nickel layer containing columnar crystals creates a modulus gradient in the thickness direction of the composite current collector, causing external forces to dissipate step by step at the interface, significantly improving the tensile strength of the composite current collector. At the same time, it can prevent the penetration of corrosive media, thereby improving the corrosion resistance of the composite current collector. Secondly, by controlling the thickness d1 of the first nickel layer and the thickness d2 of the second nickel layer to satisfy: d2 / d1=1.5~4.0, an asymmetric thickness design of the nickel layer is achieved, introducing compressive stress inside the composite current collector to offset external stress, achieve stress balance, and improve the bonding force between the first nickel layer and the metal substrate. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of a composite current collector structure; Figure 2 The XRD patterns of the first and second nickel layers in the composite current collector of Example 1 are shown. Figure 3 The image shows the EBSD spectrum of the first nickel layer in the composite current collector of Example 1. Figure 4 This is a SEM image of the second nickel layer in the composite current collector of Example 1; Figure 5 The graphs show the elongation-tensile strength of the composite current collectors in Example 1 and Comparative Example 1.
[0022] Figure description: 1. Metal base layer, 2. First nickel layer, 3. Second nickel layer. Detailed Implementation
[0023] To facilitate understanding of this application, a more complete description will be provided below. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.
[0024] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0025] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0026] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1-5” is disclosed, the described range should be interpreted as including ranges “1-4”, “1-3”, “1-2”, “1-2 and 4-5”, “1-3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0027] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0028] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has 'a' parts by mass and component B has 'b' parts by mass, it means that the mass ratio of component A to component B is a:b. It is important to understand that, unlike mass percentage content, the sum of the mass parts of all components is not limited to 100 parts.
[0029] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0030] The first aspect of this application, as Figure 1 As shown, a composite current collector is provided, comprising a metal base layer 1 and a first nickel layer 2 and a second nickel layer 3 sequentially stacked on at least one side surface of the metal base layer 1; The thickness d1 of the first nickel layer on one side and the thickness d2 of the second nickel layer on one side satisfy: d2 / d1 = 1.5~4.0; The average grain size a of the first nickel layer and the average grain size b of the second nickel layer satisfy: a <b,a<80nm; The first nickel layer has granular crystals, and the second nickel layer has columnar crystals.
[0031] Although the mechanism is not yet clear, the applicant unexpectedly discovered that: the granular crystals of the first nickel layer enhance tensile strength by hindering dislocation movement through grain boundaries; the columnar crystals of the second nickel layer grow along the thickness direction of the composite current collector, improving the fracture toughness and crack propagation resistance of the second nickel layer, thereby improving the toughness of the composite current collector; the structure formed by the first nickel layer containing granular crystals and the second nickel layer containing columnar crystals creates a modulus gradient in the thickness direction of the composite current collector, causing external forces to dissipate step by step at the interface, significantly improving the tensile strength of the composite current collector, while also preventing the penetration of corrosive media, thereby improving the corrosion resistance of the composite current collector; secondly, by controlling the thickness d1 of the first nickel layer on one side and the thickness d2 of the second nickel layer on one side to satisfy: d2 / d1=1.5~4.0, an asymmetric thickness design of the nickel layer is achieved, introducing compressive stress inside the composite current collector to offset external stress, achieving stress balance, and improving the bonding force between the first nickel layer and the metal substrate.
[0032] In any implementation, the term "stacked" refers to two layers that are directly or indirectly bonded to each other. In this context, the term "direct" means that there is no intermediate layer between the two layers, and the term "indirect" means that there is an intermediate layer between the two layers.
[0033] Specifically, d2 / d1 can be a range of values consisting of one or any two of the following: 1.5, 1.7, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, and 4.0.
[0034] In some embodiments, the thickness d1 of the first nickel layer on one side, measured in nm, satisfies: 100≤d1≤300; and the thickness d2 of the second nickel layer on one side satisfies: 300≤d2≤800.
[0035] Although the mechanism is not yet clear, the applicant unexpectedly discovered that the thicknesses of the first and second nickel layers are within the aforementioned range. Specifically, the thickness d1 of the first nickel layer on one side can be a range of values consisting of one or any two of the following: 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, and 300nm.
[0036] Specifically, the thickness of the second nickel layer on one side can be a range of one or any combination of two of the following: 300nm, 320nm, 350nm, 370nm, 400nm, 430nm, 450nm, 480nm, 500nm, 520nm, 550nm, 570nm, 600nm, 630nm, 650nm, 680nm, 700nm, 720nm, 750nm, 770nm, and 800nm.
[0037] It should be noted that scanning electron microscopy (SEM) can be used to test the thickness of the first nickel layer, the second nickel layer, the metal substrate, and the composite current collector. The testing method includes: disassembling the battery, removing the active layer on the negative electrode to expose the composite current collector, preparing a cross-sectional sample of the composite current collector using liquid nitrogen quenching or argon ion etching, and observing the secondary electronic phase morphology of the sample cross-section using a scanning electron microscope (SEM) at magnification (1000–30000x). The thickness of the first nickel layer, the second nickel layer, the metal substrate, and the composite current collector can be measured.
[0038] In some embodiments, the average grain size a of the first nickel layer, measured in nm, satisfies: 15 ≤ a ≤ 65, and the average grain size b of the second nickel layer satisfies: 70 ≤ b ≤ 185.
[0039] Although the mechanism is not yet clear, the applicant unexpectedly discovered that when the average grain size of the first nickel layer and the second nickel layer is within the above range, it can effectively increase the adhesion between the first nickel layer and the metal substrate, as well as improve the tensile strength and corrosion resistance of the composite current collector.
[0040] Specifically, the average grain size 'a' of the first nickel layer can be a range of one or any combination of two of the following: 15nm, 17nm, 19nm, 21nm, 23nm, 25nm, 27nm, 30nm, 32nm, 35nm, 37nm, 40nm, 43nm, 45nm, 48nm, 50nm, 52nm, 55nm, 57nm, and 60nm.
[0041] Specifically, the average grain size of the second nickel layer can be a range of one or any combination of two of the following: 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm, 150nm, 155nm, 160nm, 165nm, 170nm, 175nm, and 180nm.
[0042] It should be noted that a Rigaku-type X-ray diffractometer can be used to test the average grain size of the first and second nickel layers. The test method includes: disassembling the battery, removing the active layer on the negative electrode to expose the composite current collector, preparing a cross-sectional sample of the composite current collector using liquid nitrogen quenching or argon ion etching, and testing the average grain size of the cross-section of the first and second nickel layers in accordance with the standard GB / T 38532-2020 Microbeam Analysis: Determination of Average Grain Size by Electron Backscatter Diffraction.
[0043] In some embodiments, the texture factor TC(111) of the (111) crystal plane of the first nickel layer satisfies: TC(111)≥45%; the texture factor TC(200) of the (200) crystal plane of the second nickel layer satisfies: TC(200)≥38%.
[0044] Although the mechanism is not yet clear, the applicant unexpectedly discovered that the texture coefficient TC(111) of the (111) crystal plane of the first nickel layer and the texture coefficient TC(200) of the (200) crystal plane of the second nickel layer are within the above range. Through the synergistic effect between different crystal plane orientations, the high strength of the (111) crystal plane and the high toughness of the (200) crystal plane are utilized to enable the composite current collector to achieve a balance between strength and toughness, hinder crack propagation, and thus improve the tensile strength and corrosion resistance of the composite current collector.
[0045] Specifically, the texture factor TC (111) of the (111) crystal plane of the first nickel layer can be a range of one or any two of 45%, 47%, 50%, 53%, 55%, 58%, 60%, 62%, 65%, 67%, 70%, 73%, 75%, 78%, 80%, 82%, and 85%.
[0046] Specifically, the texture factor TC(200) of the (200) crystal plane of the second nickel layer can be a range of one or any two of 38%, 40%, 42%, 45%, 47%, 50%, 53%, 55%, 58%, 60%, 62%, 65%, 67%, 70%, 73%, and 75%.
[0047] It should be noted that a Rigaku-type X-ray diffractometer can be used to perform phase characterization and crystal plane analysis on the composite current collector, thereby obtaining the texture coefficients TC(220) and TC(111). The test method includes: disassembling the battery, removing the active layer on the negative electrode to expose the composite current collector, cleaning the surface of the composite current collector with 10 vol.% dilute sulfuric acid and anhydrous ethanol solution in sequence, drying it with cold air, and then testing; the test conditions include: using a copper Kα target (λ=0.15406nm), a working voltage of 40kV, a scanning angle range of 0-100°, and a scanning rate of 0.02° / s. The obtained XRD spectrum includes two characteristic peaks, corresponding to the (111) crystal plane and the (200) crystal plane, respectively. The integral intensity ratio of the (200) peak is defined as the texture coefficient TC(200) of the (200) crystal plane, and the integral intensity ratio of the (111) peak is defined as the texture coefficient TC(111) of the (111) crystal plane.
[0048] In some embodiments, the composite current collector includes a nickel-phosphorus alloy layer disposed between the metal substrate and the first nickel layer.
[0049] Although the mechanism is not yet clear, the applicant has unexpectedly discovered that setting a nickel-phosphorus alloy layer between the first nickel layer and the metal substrate can improve the adhesion between the first nickel layer and the metal substrate and prevent the first nickel layer from peeling off under stress.
[0050] In some embodiments, the thickness d3 of the nickel-phosphorus alloy layer on one side, measured in nm, satisfies: 5 ≤ d3 ≤ 20; for example, it can be a range of values consisting of one or any two of 5 nm, 7 nm, 9 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, and 20 nm.
[0051] Although the mechanism is not yet clear, the applicant has unexpectedly discovered that the thickness of the nickel-phosphorus alloy layer within the above range is beneficial to further improve the bonding strength between the first nickel layer and the metal substrate, and avoid the problems of insufficient interface reinforcement due to too small a thickness or increased internal stress due to too large a thickness.
[0052] In some embodiments, the mass percentage P of phosphorus in the nickel-phosphorus alloy layer satisfies: 4% ≤ P ≤ 10%, for example, it can be a range of one or any two of 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%.
[0053] Although the mechanism is not yet clear, the applicant unexpectedly discovered that when the mass percentage of phosphorus in the nickel-phosphorus alloy layer is within the above range, it is beneficial to form an amorphous or microcrystalline structure, thereby further improving the bonding strength and stress-relief ability between the nickel-phosphorus alloy layer and the adjacent metal layer while ensuring the uniformity of the coating and low internal stress.
[0054] In some embodiments, the thickness d4 of the metal substrate, measured in μm, satisfies: 3 ≤ d4 ≤ 8; for example, it can be a range of values consisting of one or any combination of two of the following: 3 μm, 3.2 μm, 3.5 μm, 3.7 μm, 4 μm, 4.3 μm, 4.5 μm, 4.8 μm, 5 μm, 5.2 μm, 5.5 μm, 5.7 μm, 6 μm, 6.3 μm, 6.5 μm, 6.8 μm, 7 μm, 7.2 μm, 7.5 μm, 7.7 μm, and 8 μm.
[0055] The thickness of the metal substrate is within the above range, which gives the composite current collector a moderate thickness and good mechanical properties.
[0056] In some embodiments, the first nickel layer and the second nickel layer are each made of nickel or a nickel alloy independently.
[0057] In some embodiments, the metal substrate is made of copper or a copper alloy.
[0058] Secondly, a method for preparing the aforementioned composite current collector is provided, comprising the following steps: Preparation of the first nickel layer: A first nickel layer is deposited on the surface of at least one side of the metal substrate using a first electrodeposition method; Preparation of the second nickel layer: A second nickel layer is deposited on the surface of the first nickel layer using a second electrodeposition method; In the step of preparing the first nickel layer, the first electrodeposition is carried out in the first electroplating solution, which includes 1,4-butynediol.
[0059] Although the mechanism is not yet clear, the applicant unexpectedly discovered that adding 1,4-butynediol to the first electroplating solution is beneficial to refining the coating grains and improving the leveling and brightness of the coating.
[0060] The term "electrodeposition" still refers to the process of providing electrons to an ionic metal to form a nonionic coating on a conductive surface. The corresponding system may include a chemical solution of a metal in ionic form, an anode (i.e., a negatively charged electrode corresponding to the metal to be plated), and a cathode (i.e., a positively charged electrode that provides electrons to create a nonionic metal film on the conductive surface). For electroplating or electrodeposition of metals such as copper, an aqueous solution containing the metal to be deposited as ions (particularly a dissolved metal salt) can be used. The electric field between the anode and cathode can force positively charged metal ions to move to the cathode and deposit on its surface.
[0061] The terms "electrodeposition" and "electroplution" are used interchangeably.
[0062] In some embodiments, the first electroplating solution comprises the following components at mass concentrations: nickel sulfate 200-300 g / L, nickel chloride 30-50 g / L, boric acid 30-40 g / L, saccharin 0.2-2 g / L, and 1,4-butynediol 0.05-0.5 g / L.
[0063] Specifically, in the first electroplating solution, the mass concentration of nickel sulfate can be one or any combination of two of the following: 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L, 250 g / L, 260 g / L, 270 g / L, 280 g / L, 290 g / L, and 300 g / L.
[0064] Specifically, in the first electroplating solution, the mass concentration of nickel chloride can be a range of one or any combination of two of the following: 30 g / L, 32 g / L, 34 g / L, 36 g / L, 38 g / L, 40 g / L, 42 g / L, 44 g / L, 46 g / L, 48 g / L, and 50 g / L.
[0065] Specifically, in the first electroplating solution, the mass concentration of boric acid can be a range of one or any combination of two of the following: 30 g / L, 31 g / L, 32 g / L, 33 g / L, 34 g / L, 35 g / L, 36 g / L, 37 g / L, 38 g / L, 39 g / L, and 40 g / L.
[0066] Specifically, in the first electroplating solution, the mass concentration of saccharin can be a range of one or any combination of two of the following: 0.2 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 1 g / L, 1.2 g / L, 1.4 g / L, 1.6 g / L, 1.8 g / L, and 2 g / L.
[0067] Specifically, in the first electroplating solution, the mass concentration of 1,4-butynediol can be one of the following or any combination of two values: 0.05 g / L, 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, and 0.5 g / L.
[0068] In some embodiments, the first electroplating solution further contains electroplating additives, such as gloss agents, leveling agents, or combinations thereof.
[0069] In some embodiments, the pH value of the first electroplating solution is 3.5 to 4.5, for example, it can be a range of one or any two of 3.5, 3.7, 3.9, 4.1, 4.3, and 4.5.
[0070] In some embodiments, the temperature of the first electroplating solution is 45~55°C, for example, it can be a range of one or any two of 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, and 55°C.
[0071] In some embodiments, in the step of preparing the second nickel layer, the second electrodeposition is carried out in a second electroplating solution comprising the following components at mass concentrations: nickel sulfate 250-350 g / L, nickel chloride 40-60 g / L, boric acid 35-45 g / L, and sodium dodecyl sulfate 0.05-0.2 g / L.
[0072] Specifically, in the second electroplating solution, the mass concentration of nickel sulfate can be one or any combination of two of the following: 250 g / L, 260 g / L, 270 g / L, 280 g / L, 290 g / L, 300 g / L, 310 g / L, 320 g / L, 330 g / L, 340 g / L, and 350 g / L.
[0073] Specifically, in the second electroplating solution, the mass concentration of nickel chloride can be a range of one or any combination of two of the following: 40 g / L, 42 g / L, 44 g / L, 46 g / L, 48 g / L, 50 g / L, 52 g / L, 54 g / L, 56 g / L, 58 g / L, and 60 g / L.
[0074] Specifically, in the second electroplating solution, the mass concentration of boric acid can be a range of one or any combination of two of the following: 35 g / L, 36 g / L, 37 g / L, 38 g / L, 39 g / L, 40 g / L, 41 g / L, 42 g / L, 43 g / L, 44 g / L, and 45 g / L.
[0075] Specifically, in the second electroplating solution, the mass concentration of sodium dodecyl sulfate can be one or any combination of 0.05 g / L, 0.07 g / L, 0.1 g / L, 0.13 g / L, 0.15 g / L, 0.18 g / L, 0.2 g / L.
[0076] In some embodiments, the second electroplating solution further contains electroplating additives, such as gloss agents, leveling agents, or combinations thereof.
[0077] In some embodiments, the pH value of the second electroplating solution is 4.0 to 5.0, for example, it can be a range of one or any two of 4.0, 4.2, 4.4, 4.6, 4.8, and 5.0.
[0078] In some embodiments, the temperature of the second electroplating solution is 40~70°C, for example, it can be a range of one or any two of 40°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, and 70°C.
[0079] In some embodiments, the first electrodeposition is pulse electrodeposition; the second electrodeposition is direct current electrodeposition.
[0080] In some embodiments, the process parameters for the pulse electrodeposition are as follows: current density of 5-10 A / dm³. 2 For example, it can be 5A / dm 2 6A / dm 2 7A / dm 2 8A / dm 2 9A / dm 2 10A / dm 2The range of values consisting of one or any two of the following: duty cycle is 20-50%, for example, it can be one or any two of the following: 20%, 22%, 25%, 27%, 30%, 33%, 35%, 38%, 40%, 42%, 45%, 47%, 50%; frequency is 200-500Hz; for example, it can be one or any two of the following: 200Hz, 220Hz, 250Hz, 270Hz, 300Hz, 330Hz, 350Hz, 380Hz, 400Hz, 420Hz, 450Hz, 470Hz, 500Hz.
[0081] In some embodiments, the current density of the DC electrodeposition is 2-5 A / dm³. 2 For example, it can be 2 A / dm 2 3 A / dm 2 4 A / dm 2 5 A / dm 2 The range of values consisting of one or any two of them.
[0082] In some embodiments, the step of preparing a nickel-phosphorus alloy layer is also included, which is performed before the step of preparing the first nickel layer; the step of preparing the nickel-phosphorus alloy layer is as follows: depositing the nickel-phosphorus alloy layer on the surface of at least one side of the metal substrate using a chemical deposition method.
[0083] In some embodiments, the chemical deposition is carried out in a chemical deposition solution comprising the following components at mass concentrations: nickel sulfate 20-30 g / L, sodium hypophosphite 25-35 g / L, sodium citrate 15-25 g / L, and sodium acetate 10-20 g / L.
[0084] Specifically, in the chemical deposition solution, the mass concentration of nickel sulfate can be a range of one or any combination of two of the following: 20 g / L, 21 g / L, 22 g / L, 23 g / L, 24 g / L, 25 g / L, 26 g / L, 27 g / L, 28 g / L, 29 g / L, and 30 g / L.
[0085] Specifically, in the chemical precipitation solution, the mass concentration of sodium hypophosphite can be a range of one or any combination of two of the following: 25 g / L, 26 g / L, 27 g / L, 28 g / L, 29 g / L, 30 g / L, 31 g / L, 32 g / L, 33 g / L, 34 g / L, and 35 g / L.
[0086] Specifically, in the chemical precipitation solution, the mass concentration of sodium citrate can be a range of one or any combination of 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L, 21 g / L, 22 g / L, 23 g / L, 24 g / L, and 25 g / L.
[0087] Specifically, in the chemical precipitation solution, the mass concentration of sodium acetate can be a range of one or any combination of 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, and 20 g / L.
[0088] In some embodiments, the pH value of the chemical deposition solution is 4.5 to 5.5, for example, it can be a range of one or any two of 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, and 5.5.
[0089] In some embodiments, the temperature of the chemical deposition solution is 80~90°C, for example, it can be a range of one or any combination of 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, and 90°C.
[0090] In some embodiments, the chemical deposition time is 5 to 30 seconds, for example, it can be a range of one or any combination of two of the following: 5 seconds, 7 seconds, 9 seconds, 10 seconds, 12 seconds, 15 seconds, 17 seconds, 20 seconds, 23 seconds, 25 seconds, 28 seconds, and 30 seconds.
[0091] Thirdly, a solid-state battery is provided, comprising the aforementioned composite current collector or a composite current collector prepared by the method for preparing the aforementioned composite current collector.
[0092] Unless otherwise stated, the term "solid-state battery" as used in this application refers to a battery in which the electrolyte includes a solid electrolyte.
[0093] In this application, unless otherwise specified, "solid electrolyte" refers to an electrolyte material or substance that exists in solid form during the storage and fabrication of solid-state batteries and their components, as well as during the operation of solid-state batteries. This includes, but is not limited to, solid electrolytes existing in solid form at room temperature.
[0094] Solid-state batteries include at least one electrode assembly.
[0095] In this application, unless otherwise specified, "electrode assembly" refers to a basic unit capable of converting chemical energy into electrical energy, and all components are solid-state. Non-limitingly, the electrode assembly 12 may include a positive electrode, a solid electrolyte layer, and a negative electrode, with the solid electrolyte layer located between the positive and negative electrode. During battery charging and discharging, active ions repeatedly insert and extract between the positive and negative electrode. The solid electrolyte layer serves to conduct ions between the positive and negative electrode and also isolates the positive and negative electrode, thus preventing short circuits between the positive and negative electrodes.
[0096] Furthermore, the positive electrode, the solid electrolyte layer, and the negative electrode can constitute an electrode assembly, and the actual number of electrode assemblies can be set to one or more as needed. As an example, the positive electrode includes a positive current collector and a positive active layer disposed on at least one surface of the positive current collector. As an example, the negative electrode includes a composite current collector and a negative active layer disposed on at least one surface of the composite current collector.
[0097] In some implementations, the negative electrode sheet only includes a composite current collector. In this case, the negative electrode sheet does not contain a negative electrode active layer, and the solid-state battery is a negative electrode-free solid-state battery.
[0098] As a non-limiting example, the negative electrode active layer can be disposed on two opposing surfaces of the composite current collector.
[0099] In some implementations, solid-state batteries include semi-solid-state batteries and all-solid-state batteries.
[0100] In some implementations, the solid-state battery includes an all-solid-state battery. Further, the solid-state battery is an all-solid-state battery.
[0101] It is understandable that a liquid battery refers to a battery in which the electrolyte is liquid. A semi-solid battery is a type of battery that falls between a liquid battery and a fully solid battery. It is mainly based on a liquid battery, but replaces part of the electrolyte with a solid electrolyte.
[0102] In this application, unless otherwise specified, "all-solid-state battery" refers to a solid-state battery in which all electrolytes are solid electrolytes. In this case, the positive electrode, negative electrode and electrolyte are all made of solid materials, and no liquid electrolyte is provided in the battery, so it can be called an "all-solid-state battery".
[0103] In some implementations, the solid-state battery includes a solid-state battery having a stacked structure.
[0104] In some embodiments, the positive electrode may be formed based on an etched solid electrolyte membrane or provided by a pre-fabricated positive electrode, which may be a positive electrode that is available in the art for use in solid-state batteries.
[0105] In some embodiments, the positive electrode sheet can be prepared by dry or wet methods. For example, it can be dry-pressed into a film. Alternatively, it can be wet-coated and dried to form a film.
[0106] In some embodiments, the positive electrode includes a positive current collector and a positive active layer disposed on at least one surface of the positive current collector.
[0107] Unless otherwise stated in this application, the positive electrode sheet includes at least a positive active layer.
[0108] Unless otherwise stated in this application, the positive electrode sheet includes at least a positive active layer.
[0109] In this application, unless otherwise specified, the positive electrode active layer includes at least positive electrode active particles, and usually also includes positive electrode electrolyte particles.
[0110] In this application, unless otherwise specified, "positive electrode active particles" refers to particles containing positive electrode active substances that have the ability to reversibly extract and insert active ions.
[0111] In this application, unless otherwise specified, "positive electrode electrolyte particles" and "positive electrode solid electrolyte" have the same meaning and can be used interchangeably, referring to solid electrolytes that can be used in positive electrode sheets. Positive electrode electrolyte particles can enhance the ion conductivity of positive electrode sheets, reduce interfacial impedance, and promote the charge transfer efficiency and full release of capacity between the positive electrode active material and the external environment.
[0112] In some embodiments, the positive electrode active material may be a known positive electrode active material for batteries. As a non-limiting example, the positive electrode active material may include one or more of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Non-limiting examples of lithium-containing phosphates with an olivine structure include, but are not limited to, one or more of lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium iron manganese phosphate, and lithium manganese iron phosphate and carbon composites. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O2, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi1 / 3 Co 1 / 3Mn 1 / 3 O2 (also known as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM811), etc. Non-limiting examples of lithium nickel cobalt aluminum oxides may include LiNi. 0.80 Co 0.15 Al 0.05 O2. Examples of lithium iron phosphate include LiFePO4 (also known as LFP). Examples of lithium manganese phosphate include LiMnPO4.
[0113] Without limitation, the weight percentage of positive electrode active particles or positive electrode active materials in the positive electrode active layer can be ≥70wt%, further ≥80wt%, even further ≥90wt%, and can also be 70wt%~99wt%, optionally 80wt%~95wt%.
[0114] Non-limiting, the weight percentage of positive electrode electrolyte particles in the positive electrode active layer can be 0.1wt% to 30wt%, and optionally 5wt% to 20wt%.
[0115] In some embodiments, the positive electrode active layer includes positive electrode electrolyte particles. Non-limitingly, the weight percentage of the positive electrode electrolyte particles in the positive electrode active layer can be 0.1 wt% to 30 wt%, optionally 5 wt% to 20 wt%.
[0116] In some embodiments, the positive electrode active layer includes positive electrode active particles and positive electrode electrolyte particles.
[0117] In some embodiments, the positive electrode active layer includes a conductive agent (which may be referred to as a positive electrode conductive agent). As a non-limiting example, the positive electrode conductive agent may be a carbon conductive agent. Non-limitingly, the carbon conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the positive electrode conductive agent may include, but is not limited to, one or more of SP, KS-6, acetylene black, branched Ketjen black ECP, SFG-6, vapor-grown carbon fiber VGCF, carbon nanotubes (CNTs), and graphene. Non-limitingly, the weight percentage of the positive electrode conductive agent in the positive electrode active layer may be 0-10 wt%, more further 0-8 wt%, even further 0-5 wt%, and even further 0.1 wt%-3 wt%. When the positive electrode material is prepared into a positive electrode active layer using a dry method, the positive electrode conductive agent can be incorporated into the positive electrode material, which can improve the conductivity of the positive electrode active layer.
[0118] In some embodiments, the positive electrode active layer optionally includes a binder (which may be referred to as a positive electrode binder). As a non-limiting example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. The aforementioned non-limiting examples of positive electrode binders are all organic binders and belong to organic components. Typically, the weight percentage of the positive electrode binder in the positive electrode active layer can be 0-10 wt%, more commonly 0-8 wt%, even more commonly 0.1 wt%-5 wt%, and even more commonly 1 wt%-5 wt%. When the positive electrode material is formulated into a positive electrode slurry using a wet process and then the positive electrode active layer is prepared, the positive electrode binder can be placed in the positive electrode slurry, which can assist in film formation and also promote the formation of a good electrical contact network between the active particles in the positive electrode active layer.
[0119] Non-limiting, the positive electrode active layer may include positive electrode active particles, positive electrode electrolyte particles, positive electrode conductive agent, and positive electrode binder. The types and amounts of each component can be found in the context of this application.
[0120] As a non-limiting example, the positive current collector has two surfaces that are opposite to each other in its own thickness direction, and the positive active layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0121] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. In the positive electrode current collector, the composite current collector may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. In the positive electrode current collector, the composite current collector may be obtained by forming a metal material on the polymeric material substrate. Non-limiting examples of the metal material in the positive electrode current collector may include at least one of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Non-limiting examples of the polymeric material substrate in the positive electrode current collector may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0122] In some embodiments, the positive electrode sheet can be prepared by: dry mixing the components used to prepare the positive electrode sheet, such as positive electrode active particles, positive electrode electrolyte particles, positive electrode conductive agent, positive electrode binder, and any other components; then heating and pressurizing the mixed material to knead it into a clump; hot rolling pressing to form a self-supporting positive electrode sheet; and hot rolling bonding the self-supporting positive electrode sheet with a positive electrode current collector, wherein the self-supporting positive electrode sheet can be bonded to at least one side (single or double sides) of the positive electrode current collector to obtain the positive electrode sheet. Non-limitingly, a dual planetary mixer can be used for dry mixing. Non-limitingly, a kneading and pressing process can be performed using a Banbury mixer. Non-limitingly, the temperature for hot rolling pressing can be 75°C to 85°C, and further, such as 78°C, 80°C, 82°C, etc. The method of assembling solid-state batteries using positive electrode sheets is suitable for industrial mass production.
[0123] In some embodiments, the positive electrode sheet can be prepared by dispersing the components used to prepare the positive electrode sheet, such as positive electrode active particles, positive electrode electrolyte particles, positive electrode conductive agent, positive electrode binder, and any other components, in an organic solvent to form a positive electrode slurry. Further, the positive electrode slurry is coated onto at least one surface of the positive electrode current collector, and after drying, cold pressing, and other processes, the positive electrode sheet is obtained. Cold pressing can be performed using a cold rolling mill. Non-limitingly, the organic solvent in the positive electrode slurry can include one or more of p-xylene, trimethylbenzene, butyl butyrate, heptane, etc., and more specifically, p-xylene. The surface of the positive electrode current collector coated with the positive electrode slurry can be a single surface of the positive electrode current collector or both surfaces of the positive electrode current collector. The solid content of the positive electrode slurry can be 40wt% to 80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000 mPa·s to 25000 mPa·s. When coating the positive electrode slurry, the coating density per unit area, measured by dry weight (excluding solvent), can be 15 mg / cm³, based on the amount coated on one side of the positive electrode current collector. 2 ~35mg / cm2 However, this is not the only possibility. The compaction density of the positive electrode sheet can be 3.0 g / cm³. 3 ~3.6g / cm 3 3.3g / cm³ is an option. 3 ~3.5g / cm 3 .
[0124] The term "compacted density" as used in this application has a meaning known in the art and is one of the reference indicators for the energy density of materials. In this application, unless otherwise specified, the compacted density of a positive electrode sheet or positive electrode plate refers to the ratio of the mass of the positive electrode active layer to its volume.
[0125] A solid electrolyte layer can be introduced by forming electrode layers on both sides of the solid electrolyte membrane, or it can be introduced on the electrode layer.
[0126] The solid electrolyte layer acts as a conductor of ions between the positive and negative electrodes, and can also isolate the positive and negative electrodes to prevent short circuits between them.
[0127] It is understood that the solid electrolyte layer includes a solid electrolyte. The solid electrolyte in the solid electrolyte layer can be a solid electrolyte known in the art that can be used in solid-state batteries.
[0128] The types of solid electrolytes present in different film layers of a solid-state battery can be the same or different. For example, the solid electrolytes in the positive electrode and the solid electrolyte layer can be the same or different.
[0129] As a non-limiting example, in different film layers of a solid-state battery, the solid electrolyte may include one or more of the following: sulfide solid electrolyte, halide solid electrolyte, oxide solid electrolyte, polymer solid electrolyte, etc.
[0130] As another non-limiting example, in different film layers of a solid-state battery, the solid electrolyte can be, but is not limited to, one or more of oxide-based solid electrolytes, sulfide-based solid electrolytes, and halide-based solid electrolytes. In some embodiments, the solid electrolyte can independently include, but is not limited to, one or more of Argyrodite-type sulfide electrolytes and halide electrolytes. Non-limiting examples of oxide-based solid electrolytes may include LISICON-type oxide electrolytes (such as γ-Li3PO4), NASICON-type oxide electrolytes (such as Li... 1+x Al x Ge 2-x (PO4)3, Li 1+x Al x Ti 2-x(PO4)3, etc., 0≤x≤1), Garnet type (such as Li7La3Zr2O) 12 (etc.), perovskite-type oxide electrolytes (such as Li3xLa, etc.) 2 / 3-x One or more of the following: TiO3, etc. (0≤x≤0.5). Non-limiting examples of sulfide solid electrolytes may include Li. 10 GeP2S 12 Li₂S-P₂S₅, Argyrodite type (such as Li₆PS₅Cl, Li 5.5 PS 5.5 Cl 1.5 One or more of the following (etc.). Non-limiting examples of halide solid electrolytes may include one or more of the following: Li3InCl6, Li3YCl6, Li3ScCl6, Li3ErCl6, Li2ZrCl6, etc.
[0131] Solid electrolyte membranes or solid electrolyte layers can be prepared using dry methods. In some embodiments, the solid electrolyte layer can be formed by pressing solid electrolyte materials into a solid electrolyte membrane. In other embodiments, the solid electrolyte layer is formed by pressing the constituent raw materials of the solid electrolyte layer onto an electrode layer. In still other embodiments, the solid electrolyte membrane can also be prepared using methods such as fibrosis combined with calendering, melt extrusion, or spraying.
[0132] In this application, the sheet-like solid electrolyte membrane may also be referred to as a solid electrolyte membrane sheet.
[0133] Solid electrolyte layers can also be prepared using a wet process. The electrolyte slurry used includes at least a solid electrolyte and an organic solvent, and usually also includes one or more of a binder and a dispersant.
[0134] In some embodiments, the thickness of the solid electrolyte layer can be 0.1 μm to 1000 μm, and can be selected as 10 μm to 100 μm, 100 μm to 800 μm, 500 μm to 800 μm, etc.
[0135] In some embodiments, the solid-state battery may include an outer packaging. This outer packaging may be used to encapsulate the aforementioned electrode assembly.
[0136] In some embodiments, the outer packaging of a solid-state battery can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of a solid-state battery can also be a soft pack, such as a pouch-type soft pack. The material of the soft pack can be plastic; further, non-limiting examples of plastics may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0137] This application does not impose any particular restrictions on the shape of the solid-state battery; it can be cylindrical, square, or any other arbitrary shape.
[0138] The outer packaging may include a shell and a cover. The shell may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The shell has an opening communicating with the receiving cavity, and the cover plate can be placed over the opening to close the receiving cavity. Electrode assemblies are encapsulated within the receiving cavity. The solid-state battery may contain one or more electrode assemblies, which can be selected by those skilled in the art according to actual needs.
[0139] In some implementations, solid-state batteries can be individual cells, battery modules, or battery packs.
[0140] The battery module includes at least one solid-state battery. The battery module may contain one or more solid-state batteries, and those skilled in the art can select the appropriate number based on the application and capacity of the battery module.
[0141] In a battery module, multiple solid-state batteries can be arranged sequentially along the length of the module. Alternatively, they can be arranged in any other manner. Furthermore, these multiple solid-state batteries can be secured using fasteners.
[0142] Optionally, the battery module may also include a housing with a receiving space in which multiple solid-state batteries are housed.
[0143] In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more. Those skilled in the art can select an appropriate number according to the application and capacity of the battery pack.
[0144] The battery pack may include a battery box and multiple battery modules disposed within the battery box. The battery box includes an upper body and a lower body, with the upper body covering the lower body to form a closed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.
[0145] A fourth aspect of this application provides an electrical device including the solid-state battery described in the third aspect of this application.
[0146] In some embodiments, the electrical device includes at least one of the solid-state batteries of any of the embodiments provided in this application.
[0147] Without limitation, solid-state batteries can be used as a power source for an electrical device or as an energy storage unit for an electrical device. Electrical devices can include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be, for example, mobile phones, laptops, etc.; electric vehicles can be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.
[0148] As an electrical device, solid-state batteries can be selected based on its usage requirements.
[0149] This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density batteries, a battery pack or battery module can be used.
[0150] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a battery as their power source.
[0151] Example 1 This embodiment provides a method for preparing a composite current collector, including the following steps: S1: A 6μm thick lithium battery copper foil is degreased with acetone, activated with 10 vol.% dilute sulfuric acid for 30s, rinsed with deionized water, and dried with cold air to obtain a metal base layer. S2: The metal substrate is immersed in the first electroplating solution, and a first nickel layer is deposited on both sides of the surface of the metal substrate using a pulse electroplating method to obtain the first copper foil; wherein, the formula of the first electroplating solution is as follows: nickel sulfate 250 g / L, nickel chloride 40 g / L, boric acid 35 g / L, saccharin 1 g / L, 1,4-butynediol 0.3 g / L; the pH value of the first electroplating solution is 4.0, and the temperature of the first electroplating solution is 50℃; the parameters of the pulse electroplating are as follows: current density 6 A / dm², duty cycle 30%, frequency 200 Hz, deposition time 30s; S3: Immerse the first copper foil in the second electroplating solution, and deposit a second nickel layer on the surface of the first nickel layer using a direct current electroplating method to obtain the second copper foil; wherein, the formula of the second electroplating solution is as follows: nickel sulfate 300 g / L, nickel chloride 50 g / L, boric acid 40 g / L, sodium dodecyl sulfate 0.1 g / L, the pH value of the second electroplating solution is 4.5, and the temperature of the second electroplating solution is 55℃; the parameters of the direct current electroplating are as follows: current density 3 A / dm², deposition time 60 s; S4: Immerse the second copper foil in a 0.5% (w / w) benzotriazole anti-oxidation solution for 30 seconds, then wash with water and dry with hot air; the resulting structure is as follows. Figure 1 The composite current collector is shown in Table 1.
[0152] Example 2 This embodiment provides a method for preparing a composite current collector, including the following steps: S1: A 6μm thick lithium battery copper foil is degreased with acetone, activated with 10 vol.% dilute sulfuric acid for 30s, rinsed with deionized water, and dried with cold air to obtain a metal base layer. S2: The metal substrate is immersed in a chemical deposition solution for 15 seconds to deposit a nickel-phosphorus alloy layer with a thickness of 10 nm on both sides of the surface of the metal substrate, thus obtaining the first copper foil; wherein, the chemical deposition solution has the following formula: nickel sulfate 25 g / L, sodium hypophosphite 30 g / L, sodium citrate 20 g / L, sodium acetate 15 g / L, pH value of chemical deposition solution is 5.0, and temperature of chemical deposition solution is 85℃; S3: The first copper foil is immersed in the first electroplating solution, and a first nickel layer is deposited on the surface of the nickel-phosphorus alloy layer using a pulse electroplating method to obtain the second copper foil; wherein, the formula of the first electroplating solution is as follows: nickel sulfate 250 g / L, nickel chloride 40 g / L, boric acid 35 g / L, saccharin 1 g / L, 1,4-butynediol 0.3 g / L; the pH value of the first electroplating solution is 4.0, and the temperature of the first electroplating solution is 50℃; the parameters of the pulse electroplating are as follows: current density 6 A / dm², duty cycle 30%, frequency 200 Hz, deposition time 30s; S4: Immerse the second copper foil in the second electroplating solution, and deposit the second nickel layer on the surface of the first nickel layer using a direct current electroplating method to obtain the third copper foil; wherein, the formula of the second electroplating solution is as follows: nickel sulfate 300 g / L, nickel chloride 50 g / L, boric acid 40 g / L, sodium dodecyl sulfate 0.1 g / L, the pH value of the second electroplating solution is 4.5, and the temperature of the second electroplating solution is 55℃; the parameters of the direct current electroplating are as follows: current density 3 A / dm², deposition time 60 s; S5: Immerse the third copper foil in a 0.5% benzotriazole anti-oxidation solution for 30 seconds, wash with water, and dry with hot air to obtain the composite current collector; the performance parameters of the composite current collector are shown in Table 1.
[0153] Examples 3-5 This embodiment provides a method for preparing a composite current collector, which differs from Embodiment 1 in that the pulse electroplating and DC electroplating times are different.
[0154] Specifically, in Example 3, the pulse electroplating time is 24s and the DC electroplating time is 67s.
[0155] In Example 4, the pulse electroplating time was 22s and the DC electroplating time was 72s.
[0156] In Example 5, the pulse electroplating time was 45s and the DC electroplating time was 54s.
[0157] Examples 6-9 This embodiment provides a method for preparing a composite current collector, which differs from Example 1 in that the mass concentrations of saccharin and 1,4-butynediol in the first electroplating solution are different.
[0158] Specifically, in the first electroplating solution of Example 6, the mass concentration of saccharin was 1.2 g / L and the mass concentration of 1,4-butynediol was 0.35 g / L.
[0159] In the first electroplating solution of Example 7, the mass concentration of saccharin was 0.8 g / L and the mass concentration of 1,4-butynediol was 0.25 g / L.
[0160] In the first electroplating solution of Example 8, the mass concentration of saccharin was 1.5 g / L and the mass concentration of 1,4-butynediol was 0.45 g / L.
[0161] In the first electroplating solution of Example 9, the mass concentration of saccharin was 0.2 g / L and the mass concentration of 1,4-butynediol was 0.05 g / L.
[0162] Examples 10-12 This embodiment provides a method for preparing a composite current collector, which differs from Embodiment 1 in that the temperature of the second electroplating solution is different.
[0163] Specifically, in Example 10, the temperature of the second electroplating solution is 50°C.
[0164] In Example 11, the temperature of the second electroplating solution was 40°C.
[0165] In Example 12, the temperature of the second electroplating solution was 70°C.
[0166] Example 13 This embodiment provides a method for preparing a composite current collector, which differs from Embodiment 1 in that step S2 is different; Specifically, step S2 in Example 13 is as follows: A metal substrate is immersed in a first electroplating solution, and a first nickel layer is deposited on both sides of the surface of the metal substrate using a direct current electroplating method to obtain a first copper foil. The formulation of the first electroplating solution is as follows: nickel sulfate 250 g / L, nickel chloride 40 g / L, boric acid 35 g / L, saccharin 1 g / L, 1,4-butynediol 0.3 g / L; the pH value of the first electroplating solution is 4.0, and the temperature of the first electroplating solution is 50℃; the parameters of the direct current electroplating are as follows: current density 5 A / dm², deposition time 30 s.
[0167] Examples 14-15 This embodiment provides a method for preparing a composite current collector, which differs from Embodiment 1 in that the thickness of the lithium battery copper foil is different.
[0168] Specifically, in Example 14, the thickness of the lithium battery copper foil is 4.5 μm.
[0169] Specifically, in Example 15, the thickness of the lithium battery copper foil is 8 μm.
[0170] Comparative Example 1 The composite current collector used in this comparative example is a commercially available 6 μm double-sided photoelectrolytic copper foil with no surface coating.
[0171] Comparative Example 2 The composite current collector of this comparative example was prepared according to the method of Example 1 in Patent 202010240309.3. The copper-nickel alloy foil of the obtained copper-nickel alloy foil had a thickness of 6 μm and a nickel content of 7.2%.
[0172] Comparative Example 3 This comparative example provides a method for preparing a composite current collector, which differs from Example 1 in that: (1) The pulse electroplating time in Comparative Example 3 was 55 s; (2) Comparative Example 3 eliminated the DC electroplating step, that is, eliminated step S3 and directly applied the first copper foil obtained in step S2 to step S4.
[0173] Comparative Examples 4-6 This comparative example provides a method for preparing a composite current collector, which differs from Example 1 in that the pulse electroplating and DC electroplating times are different.
[0174] Specifically, in Comparative Example 4, the pulse electroplating time was 15s and the DC electroplating time was 90s.
[0175] In Comparative Example 5, the pulse electroplating time was 16s and the DC electroplating time was 79s.
[0176] In Comparative Example 6, the pulse electroplating time was 45s and the DC electroplating time was 30s.
[0177] Comparative Example 7 This comparative example provides a method for preparing a composite current collector, which differs from Example 1 in that the mass concentrations of saccharin and 1,4-butynediol in the first electroplating solution are different.
[0178] The mass concentration of saccharin in the first electroplating solution of Comparative Example 7 was 0 g / L, and the mass concentration of 1,4-butynediol was 0 g / L; that is, no saccharin and 1,4-butynediol were added to the first electroplating solution of Comparative Example 7.
[0179] Comparative Example 8 This comparative example provides a method for preparing a composite current collector, which differs from Example 1 in that steps S2 and S3 are different. In Comparative Example 8, steps S2 and S3 are as follows: S2: The metal substrate is immersed in the second electroplating solution, and a first nickel layer is deposited on the surface of the metal substrate using a direct current electroplating method to obtain a first copper foil; wherein, the formula of the second electroplating solution is as follows: nickel sulfate 300 g / L, nickel chloride 50 g / L, boric acid 40 g / L, sodium dodecyl sulfate 0.1 g / L, the pH value of the second electroplating solution is 4.5, and the temperature of the second electroplating solution is 55℃; the parameters of the direct current electroplating are as follows: current density 3 A / dm², deposition time 60 s; S3: Immerse the first copper foil in the first electroplating solution, and deposit a second nickel layer on both sides of the surface of the first nickel layer using a pulse electroplating method to obtain the second copper foil; wherein, the formula of the first electroplating solution is as follows: nickel sulfate 250 g / L, nickel chloride 40 g / L, boric acid 35 g / L, saccharin 1 g / L, 1,4-butynediol 0.3 g / L; the pH value of the first electroplating solution is 4.0, and the temperature of the first electroplating solution is 50℃; the parameters of the pulse electroplating are as follows: current density 6 A / dm², duty cycle 30%, frequency 200 Hz, deposition time 30s.
[0180] The performance parameters of the composite current collectors prepared in Examples 1-15 and Comparative Examples 1-8 are shown in Table 1.
[0181] Performance testing (1) Test method for the thickness of the first nickel layer, the second nickel layer and the metal substrate: The cross-sectional sample of the composite current collector is prepared by liquid nitrogen quenching or argon ion etching. The secondary electronic phase morphology of the sample cross-section is observed by scanning electron microscopy (SEM) magnification (1000 to 30000 times). The first nickel layer, the second nickel layer and the metal substrate can be measured.
[0182] (2) Test method for the average grain size of the first and second nickel layers: Cross-sectional samples of the composite current collector were prepared using liquid nitrogen quenching or argon ion etching. The average grain size of the cross-sections of the first and second nickel layers was tested in accordance with the standard GB / T38532-2020, "Determination of Average Grain Size by Electron Backscatter Diffraction in Microbeam Analysis".
[0183] (3) Test method for the texture coefficient of the (111) crystal plane of the first nickel layer and the (200) crystal plane of the second nickel layer: The surface phases and crystal planes of the first and second nickel layers in the composite current collector were characterized and analyzed using a Rigaku X-ray diffractometer. A copper Kα target (λ=0.15406nm) was used, with a working voltage of 40kV, a scanning angle range of 0-100°, and a scanning rate of 0.02° / s. The obtained XRD pattern included two characteristic peaks, corresponding to the (111) crystal plane and the (200) crystal plane, respectively. The integral intensity ratio of the (200) peak was defined as the texture coefficient TC(200) of the (200) crystal plane, and the integral intensity ratio of the (111) peak was defined as the texture coefficient TC(111) of the (111) crystal plane.
[0184] (4) Test method for tensile strength of composite current collector: According to GB / T29847 Test Standard for Copper Foil for Printed Boards, the composite current collector was stamped into a dumbbell shape (gauge length 50mm, gauge width 3mm). The sample was then fixed on the clamp of the universal testing machine. The tensile speed was set to 50mm / min and the gauge length between the clamps was 50mm. An axial tensile test was performed, and the elongation-tensile strength curve was plotted.
[0185] (5) Cohesion: Referring to GB / T29847, the standard for testing copper foil for printed circuit boards, 200 mm × 20 mm specimens were cut from the composite current collector both longitudinally and transversely. At least four 3.0 mm wide strips were prepared on each specimen. One end of each strip was peeled off no more than 13 mm and clamped onto the fixture of a universal testing machine. The other end was secured with a clamping device, ensuring the strip was in a vertical position with the metal chain free and the tilt angle ≤ ±5°. The peeling speed was set to 50 mm / min, and the strip was stretched vertically until a peel length of 25 mm was achieved. The minimum load during the process was recorded, and the actual width of the strip was measured. The peel strength (N / mm) was calculated.
[0186] (6) Corrosion resistance: The composite current collector was placed in a simulated sulfide electrolyte environment (1% H2S atmosphere, 85% relative humidity, 60℃) for 500 hours to obtain the sample to be tested. The tensile strength of the sample to be tested was tested according to the tensile strength test method. Corrosion resistance rate = tensile strength after corrosion / tensile strength before corrosion × 100%.
[0187] The test results are shown in Table 2 and Figures 2-4 As shown.
[0188] Table 1 Table 2 The experimental data in Tables 1 and 2 show that the tensile strength of the composite current collector in Examples 1-15 is ≥540MPa, the corrosion resistance is ≥82%, and the bonding force between the metal base layer and the first nickel layer is ≥0.65N / mm; indicating that the composite current collector of this application has high mechanical properties, bonding force and corrosion resistance.
[0189] Compared with Examples 1-15, the composite current collectors of Comparative Examples 1 and 2 are copper-nickel alloy foils prepared by existing technology, with tensile strength <515MPa and corrosion resistance <78.5%; indicating that the copper-nickel alloy foils prepared by existing technology have poor mechanical properties and corrosion resistance as current collectors.
[0190] Compared with Examples 1-15, the composite current collector of Comparative Example 3 does not include the second nickel layer. Its tensile strength is 435 MPa, its corrosion resistance is 81.6%, and the bonding force between the metal base layer and the first nickel layer is 0.62 N / mm. This shows that the absence of the second nickel layer in the composite current collector will lead to a decrease in the mechanical properties and corrosion resistance of the composite current collector, as well as a decrease in the bonding force between the metal base layer and the first nickel layer.
[0191] Compared with Examples 1-15, in the composite current collectors of Comparative Examples 4-6, the thickness ratio (d2 / d1) of the second nickel layer to the first nickel layer is less than 1.5 or greater than 4.0, the tensile strength is <515MPa, the corrosion resistance is <78.5%, and the bonding force between the metal substrate and the first nickel layer is ≤0.62 N / mm. This indicates that the thickness ratio between the second nickel layer and the first nickel layer is not within the protection scope of this case, which will lead to a decrease in the mechanical properties and corrosion resistance of the composite current collector, as well as a decrease in the bonding force between the metal substrate and the first nickel layer.
[0192] Compared with Examples 1-15, in the composite current collector of Comparative Example 7, the average grain size of the first nickel layer is greater than 80 nm, the tensile strength is 465 MPa, the corrosion resistance is 77%, and the bonding force between the metal substrate and the first nickel layer is 0.48 N / mm. This indicates that the average grain size of the first nickel layer in the composite current collector being greater than 80 nm will lead to a decrease in the mechanical properties and corrosion resistance of the composite current collector, as well as a decrease in the bonding force between the metal substrate and the first nickel layer.
[0193] Compared with Examples 1-15, in the composite current collector of Comparative Example 8, the positions of the first nickel layer and the second nickel layer were interchanged. The tensile strength was 478 MPa, the corrosion resistance rate was 77.8%, and the bonding force between the metal base layer and the first nickel layer was 0.53 N / mm. This shows that only by placing the first nickel layer between the metal base layer and the second nickel layer can a composite current collector with good mechanical properties and corrosion resistance, as well as high bonding force between the metal base layer and the first nickel layer, be obtained.
[0194] Figure 2 The XRD patterns of the first and second nickel layers in the composite current collector of Example 1 are shown. Figure 2 As can be seen from the diagram, the first nickel layer has a preferred orientation on the (111) plane, and the second nickel layer has a preferred orientation on the (200) crystal plane.
[0195] Figure 3 The EBSD spectrum of the first nickel layer in the composite current collector of Example 1; from Figure 3 As can be seen, the first nickel layer has dense granular crystals.
[0196] Figure 4 This is a SEM image of the second nickel layer in the composite current collector of Example 1; from Figure 4 It can be seen that the second nickel layer has columnar crystals.
[0197] Figure 5 The graph shows the elongation-tensile strength curves of the composite current collectors of Example 1 and Comparative Example 1. As can be seen from the graph, the tensile strength of the composite current collector of Example 1 is significantly increased compared with Comparative Example 1.
[0198] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of this application and not to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A composite current collector, characterized in that, It includes a metal base layer and a first nickel layer and a second nickel layer sequentially stacked on at least one surface of the metal base layer; The thickness d1 of the first nickel layer on one side and the thickness d2 of the second nickel layer on one side satisfy: d2 / d1 = 1.5~4.0; The average grain size a of the first nickel layer and the average grain size b of the second nickel layer satisfy: a <b,a<80nm; The first nickel layer has granular crystals, and the second nickel layer has columnar crystals.
2. The composite current collector as described in claim 1, characterized in that, In nm, the thickness d1 of the first nickel layer on one side satisfies: 100≤d1≤300; the thickness d2 of the second nickel layer on one side satisfies: 300≤d2≤800.
3. The composite current collector as described in claim 1, characterized in that, In nm, the average grain size a of the first nickel layer satisfies: 15≤a≤65, and the average grain size b of the second nickel layer satisfies: 70≤b≤185.
4. The composite current collector as described in claim 1, characterized in that, The texture factor TC(111) of the (111) crystal plane of the first nickel layer satisfies: TC(111)≥45%; the texture factor TC(200) of the (200) crystal plane of the second nickel layer satisfies: TC(200)≥38%.
5. The composite current collector as described in claim 1, characterized in that, The composite current collector includes a nickel-phosphorus alloy layer, which is disposed between the metal base layer and the first nickel layer.
6. The composite current collector as described in claim 5, characterized in that, In nm, the thickness d3 of the nickel-phosphorus alloy layer on one side satisfies: 5≤d3≤20; And / or, the mass percentage P of phosphorus in the nickel-phosphorus alloy layer satisfies: 4% ≤ P ≤ 10%.
7. The composite current collector as described in claim 1, characterized in that, Satisfy at least one of the following (a) to (c): (a) In μm, the thickness d4 of the metal substrate satisfies: 3≤d4≤8; (b) The first nickel layer and the second nickel layer are each made of nickel or a nickel alloy independently; (c) The metal base layer is made of copper or copper alloy.
8. A method for preparing a composite current collector as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Preparation of the first nickel layer: A first nickel layer is deposited on the surface of at least one side of the metal substrate using a first electrodeposition method; Preparation of the second nickel layer: A second nickel layer is deposited on the surface of the first nickel layer using a second electrodeposition method; In the step of preparing the first nickel layer, the first electrodeposition is carried out in the first electroplating solution, which includes 1,4-butynediol.
9. The method for preparing the composite current collector as described in claim 8, characterized in that, The first electroplating solution comprises the following components in mass concentrations: nickel sulfate 200-300 g / L, nickel chloride 30-50 g / L, boric acid 30-40 g / L, saccharin 0.2-2 g / L, and 1,4-butynediol 0.05-0.5 g / L.
10. The method for preparing the composite current collector as described in claim 8, characterized in that, In step S3, the second electrodeposition is carried out in the second electroplating solution, which comprises the following components at mass concentrations: nickel sulfate 250-350 g / L, nickel chloride 40-60 g / L, boric acid 35-45 g / L, and sodium dodecyl sulfate 0.05-0.2 g / L.
11. The method for preparing the composite current collector as described in claim 8, characterized in that, The first electrodeposition is pulse electrodeposition; the second electrodeposition is direct current electrodeposition.
12. The method for preparing the composite current collector as described in claim 11, characterized in that, The process parameters for pulse electrodeposition are as follows: current density is 5-10 A / dm³. 2 The duty cycle is 20-50%, and the frequency is 200-500Hz.
13. The method for preparing the composite current collector according to any one of claims 8 to 12, characterized in that, It also includes the step of preparing a nickel-phosphorus alloy layer, which is performed before the step of preparing the first nickel layer; the step of preparing the nickel-phosphorus alloy layer is as follows: depositing a nickel-phosphorus alloy layer on the surface of at least one side of the metal substrate using a chemical deposition method.
14. The method for preparing the composite current collector as described in claim 13, characterized in that, The chemical deposition is carried out in a chemical deposition solution comprising the following components at mass concentrations: nickel sulfate 20-30 g / L, sodium hypophosphite 25-35 g / L, sodium citrate 15-25 g / L, and sodium acetate 10-20 g / L.
15. A solid-state battery, characterized in that, The composite current collector includes the composite current collector as described in any one of claims 1 to 7 or the composite current collector prepared by the preparation method of the composite current collector as described in any one of claims 8 to 14.
16. An electrical appliance, characterized in that, Including the solid-state battery as described in claim 15.
Citation Information
Patent Citations
Copper-nickel alloy foil and electro-deposition preparation method thereof
CN111321437A